PENERAPAN PENGGUNAAN METODE SNOWBALL THROWING PADA MATA PELAJARAN BAHASA INDONESIA - Sa’diyah, Maemunah; Rodiah, Siti (ATTA`DIB, 2015)
The purposes of this study are; to know application of Snowball Throwing method, the achievement and its impact to Indonesian Lesson using such method in SDIT Ummul Quro Bogor. This study conducted a class action research. The application of Snowball Throwing method gives a good impact to Indonesian Lesson. This can be seen from the increasing the percentage of affective from 76 % in first cycle to 83 % in second one. The achievement of students increased from 56,67 % and average is 73,83 to 93,33% and average is 84. The Application of Snowball Throwing method give a rapid impact to the achievement of students.